The COVID-19 pandemic and vaccination abandonment in children: spatial heterogeneity maps - Rayssa Nogueira Rodrigues; Gabriela Lourença Martins do Nascimento; Luiz Henrique Arroyo; Ricardo Alexandre Arcêncio; Valéria Conceição de Oliveira; Eliete Albano de Azevedo Guimarães (Universidade de São Paulo, 2022)
Abstract Objective: to identify spatial clusters corresponding to abandonment of routine vaccines in children. Method: an ecological study, according to data from the 853 municipalities of a Brazilian state. The records analyzed were those of the multidose pentavalent, pneumococcal 10-valent, inactivated poliomyelitis and oral human rotavirus vaccines of 781,489 children aged less than one year old. The spatial scan statistics was used to identify spatial clusters and assess the relative risk based on the vaccination abandonment indicator. Results: the spatial scan statistics detected the presence of statistically significant clusters for abandonment regarding the four vaccines in all the years analyzed. However, the highest number of clusters with high relative risk estimates was identified in 2020. The Vale do Aço and West, North and West, and Southwest regions stand out for the pentavalent, poliomyelitis and rotavirus vaccines, respectively. Conclusion: in an attempt to mitigate the devastating impact of the COVID-19 pandemic, the immunization program experienced setbacks. The presence of clusters points to the need to implement integrated strategies that may involve different sectors for an active search for children and prevent outbreaks of vaccine-preventable diseases in the near future.